Madurese Islam: Dissemination of ‎Multicultural Education in Islamic Religious ‎Streams - Dannur, Moh; Cholily, Yus Mochamad; Khozin, Khozin; Hasan, Nor; Imamuddin (TADRIS: Jurnal Pendidikan Islam, 2023)
Multicultural education is an alternative to build togetherness in the diversity of society, and multiculturalism requires the accommodation of minority rights, both cultural and social. This research focuses on constructing a multicultural understanding of religious sects disseminated through religious sects. The research aims to describe the multicultural education of religious understanding that aims to build social harmony amid the diversity of religious sects in Sana Daja village. This research approach uses qualitative ethnography type. The data sources in this research are leaders of religious organizations, heads of religious activities, kyai, lora, and people who know the changes in interaction between religious sects in the research location. The results showed that some religious groups in the village of Sana Daja disseminate multiculturalism through religious activities such as recitation, traditions, or community social activities; religious sects become instruments of social power to instill multicultural awareness. The construction of multicultural education between religious views begins with recategorization and desacralization, explaining the various interpretations of fiqh, emphasizing the substance and purpose of religious activities, and placing religious traditions as part of ijtihad products in the practical realm. This multicultural awareness construction can slowly open the isolation of minority religious groups, build communication between religious groups that have been constrained due to conflict, and foster an attitude of tolerance so that awareness is born to build ukhuwah Islamiyah in society.